Silicon solar cells based on all‐laser‐transferred contacts. (19th July 2013) - Wang, Longteng; Carlson, David E.; Gupta, Mool C.
ABSTRACT Crystalline silicon solar cells based on all‐laser‐transferred contacts (ALTC) have been fabricated with both front and rear metallization achieved through laser induced forward transferring. Both the front and rear contacts were laser‐transferred from a glass slide coated with a metal layer to the silicon substrate already processed with emitter formation, surface passivation, and antireflection coating. Ohmic contacts were achieved after this laser transferring. The ALTC solar cells were fabricated on chemically textured p‐type Cz silicon wafers. An initial conversion efficiency of over 15% was achieved on a simple cell structure with full‐area emitter. Further improvements are expected with optimized laser transferring conditions, front grid pattern design, and surface passivation. The ALTC process demonstrates the advantage of laser processing in simplifying the solar cell fabrication by a one‐step metal transferring and firing process. Copyright © 2013 John Wiley & Sons, Ltd.